Barriers and facilitators to cervical cancer screening among under-screened women in Cuenca, Ecuador: the perspectives of women and health professionals - Bernardo Vega Crespo; Vivian Alejandra Neira; José Ortíz Segarra; Andrés Andrade; Gabriela Guerra; Stalin Ortiz; Antonieta Flores; Lorena Mora; Veronique Verhoeven; Ana Gama; Sónia Dias; Bo Verberckmoes; et al. (BMC Public Health, 2022)
Abstract Background Cervical cancer screening is a cost-effective method responsible for reducing cervical cancer-related mortality by 70% in countries that have achieved high coverage through nationwide screening strategies. However, there are disparities in access to screening. In Ecuador, although cervical cancer is the second most common cancer in women, only 58.4% of women of reproductive age have ever been screened for cervical cancer. Methodology A qualitative study was performed to understand the current barriers to screening and to identify strategies that could increase uptake in Azuay province, Ecuador. Seven focus group discussions (FGDs) were conducted with under-screened women and health professionals (HPs). The FGDs were recorded and transcribed. Content analysis was done using the socio-ecological framework to categorize and analyse the data. Results Overall, 28 women and 27 HPs participated in the study. The two groups perceived different barriers to cervical cancer screening. The HPs considered barriers to be mainly at the policy level (lack of a structured screening plan; lack of health promotion) and the individual level (lack of risk perception; personal beliefs). The women identified barriers mainly at organizational level, such as long waiting times, lack of access to health centres, and inadequate patient–physician communication. Both groups mentioned facilitators at policy level, such as national campaigns promoting cervical cancer screening, and at community and individual level, including health literacy and women’s empowerment. Conclusions The women considered access to health services the main barrier to screening, while the HPs identified a lack of investment in screening programmes and cultural patterns at the community level as major obstacles. To take an integrated approach to cervical cancer prevention, the perspectives of both groups should be taken into account. Additionally, new strategies and technologies, such as self-administered human papillomavirus (HPV) testing and community participation, should be implemented to increase access to cervical cancer screening.